The Bay Area Verbal Learning Test (BAVLT): Normative Data and the Effects of Repeated Testing, Simulated Malingering, and Traumatic Brain Injury - Woods, David L.; Wyma, John M.; Herron, Timothy J.; Yund, E. William (Frontiers in Human Neuroscience, 2017)
Verbal learning tests (VLTs) are widely used to evaluate memory deficits in neuropsychiatric and developmental disorders. However, their validity has been called into question by studies showing significant differences in VLT scores obtained by different examiners. Here we describe the computerized Bay Area Verbal Learning Test (BAVLT), which minimizes inter-examiner differences by incorporating digital list presentation and automated scoring. In the 10-minute BAVLT, a 12-word list is presented on three acquisition trials, followed by a distractor list, immediate recall of the first list, and, after a 30-minute delay, delayed recall and recognition. In Experiment 1, we analyzed the performance of 195 participants ranging in age from 18 to 82 years. Acquisition trials showed strong primacy and recency effects, with scores improving over repetitions, particularly for mid-list words. Inter-word intervals (IWIs) increased with successive words recalled. Omnibus scores (summed over all trials except recognition) were influenced by age, education, and sex (women outperformed men). In Experiment 2, we examined BAVLT test-retest reliability in 29 participants tested with different word lists at weekly intervals. High intraclass correlation coefficients were seen for omnibus and acquisition scores, IWIs, and a categorization index reflecting semantic reorganization. Experiment 3 examined the performance of Experiment 2 participants when feigning symptoms of traumatic brain injury. Although 37% of simulated malingerers showed abnormal (p < 0.05) omnibus z-scores, z-score cutoffs were ineffective in discriminating abnormal malingerers from control participants with abnormal scores. In contrast, four malingering indices (recognition scores, primacy/recency effects, learning rate across acquisition trials, and IWIs) discriminated the two groups with 80% sensitivity and 80% specificity. Experiment 4 examined the performance of a small group of patients with mild or severe TBI. Overall, both patient groups performed within the normal range, although significant performance deficits were seen in some patients. The BAVLT holds the promise of improving the speed and replicability of verbal learning assessments while providing comprehensive timing, semantic organization, and primacy/recency measures that clarify the nature of performance.